Maternal investment and growth performance of lambs in a hair coat sheep breed raised in equatorial semi-arid environment - Silva, Josinaldo Araujo da; Saraiva, Edilson Paes; Bispo, Safira Valenca; Carvalho Fonseca, Vinicius de Franca [UNESP]; Caetano Goncalves dos Santos, Severino Guilherme; Cavalcante dos Santos, Jose Danrley; Pinheiro, Antonio da Costa; Vieira Almeida, Maria Elivania (Taylor & Francis Ltd, 2020)
Thirty four lambs and twenty multiparous Morada Nova ewes with 3 +/- 1.2 years of age were evaluated in a semi-extensive system for assessments of their suckling activities when they were 10-40 days old. The body mass (kg) and biometric measurements were also assessed at each 15 days from birth to 90 days of age. From 15 to 90 days of age, single lambs had superior (P < 0.05) body mass than those twins. Both for single and twins the daily weight gain substantially decreased (P < 0.05) after thirty days of age. There was a high correlation (i.e., r > 0.90; P < 0.05) between all biometric measurements and body mass of lambs. Both for single and twins the frequency of suckling decreases (P < 0.05) as the lambs grows older. At 20 days, mothers of twin lambs prevented more (P < 0.05) the suckling attempts than those of single lambs. Both for single and twin lambs the suckling success was lower (P < 0.05) when they were 20 days of age. The present study sheds some light on how the dynamics between growth performance of Morada Nova lambs and the maternal investment are linked
Keywords: Mother-offspring relationship; body mass; naturalized sheep; caatinga biome